The Forestry Sector in India's State Action Plans on Climate Change: A Forward-Looking Analysis - Toepper, Janek; Burnwal, Kundan Kumar (Indian Forester, 2020)
With ever more manifest climate change impacts, India plays a key role in achieving the temperature goal. Within India, the forestry sector is particularly important for the achievement of domestic mitigation pledges such as the NDC forestry targets and necessary reductions in the climate vulnerabilities of rural livelihoods. Owing to India's federal structure, subnational action is the main determinant of success of climate action in the forestry sector. In a systematic literature review, we therefore here compare the forestry components of all 33 State Action Plans on Climate Change (SAPCC). In conjunction with insights from the plan implementation period, this comparison holds important lessons for the ongoing revision of the plans. These pertain inter alia to the need for scientifically rigorous methods of assessment of vulnerabilities of forest ecosystems and dependent communities, the need for specific, measurable, actionable, realistic and time-bound (SMART) targets and strategies informed by these assessments, the need to concentrate efforts and resources on synergistic approaches with adaptation and mitigation benefits, and the opportunity to develop rigorous M&E approaches for both these fields in the forestry sector. With the imminent second round of SAPCCs, state forest departments and other stakeholders should adhere to established best practices.